A study on irrigation efficiency for paddy in sekuduk chupak paddy plantation scheme - Kevin Kamarau, ak Kenneth. (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study is to find out the irrigation efficiency of Sekuduk Chupak Paddy Plantation Scheme by using Conventional Irrigation Efficiency. The value of irrigation efficiency is determined by taking the ratio of Net Irrigation Requirement (NIR) to the Net Irrigation Application (NIA) and expressed as percentage. Surface irrigation or pond irrigation is the applied irrigation system at the scheme. There are 3 irrigation ponds at the sceme, namely Pond A, Pond B and Pond D. From the results, the irrigation efficiency for irrigated area is considered very low wit measured values of 12%, 27% and 22% respectively.